Assessment of Key Competencies for Sustainability in Higher Education: A Systematic Review of Instruments and Psychometric Evidence (Papeles, 2026)
Introduction: The assessment of key competencies for sustainability in higher education shows significant conceptual advances but also important methodological gaps. This systematic review examines how key competencies for sustainability have been assessed and what type of psychometric evidence recent studies report. Methodology: Following the PRISMA 2020 statement and applying strict eligibility criteria, the Scopus, Dimensions, SciELO, Redalyc, and ERIC databases were consulted. The analysis combined a bibliometric study of 294 documents and a final content analysis of 8 studies evaluated using the Cosmin Risk of Bias Checklist. The synthesis of results was developed using a descriptive and comparative approach. Results and discussion: The findings show a predominance in the use of questionnaires and a concentration of validation processes such as reliability and content validity. Structural validity is heterogeneous and, in some cases, limited. Conclusions: Overall, the results underscore the need to strengthen conceptual standardization and diversify assessment strategies beyond self-perception. The main limitation lies in the restriction to five databases. This review was not registered in a public database of protocols.
Keywords: Key competencies for sustainability; higher education; assessmen; questionnaire; sustainable development